Reduced Frontal Brain Volume in Non-Treatment-Seeking Cocaine-Dependent Individuals: Exploring the Role of Impulsivity, Depression, and Smoking - Crunelle, Cleo L.; Kaag, Anne Marije; Van Wingen, Guido; van den Munkhof, Hanna E.; Homberg, Judith; Reneman, Liesbeth; Van Den Brink, Wim (Frontiers in Human Neuroscience, 2014)
In cocaine-dependent patients, grey matter (GM) volume reductions have been observed in the frontal lobes that are associated with duration of cocaine use. Studies are mostly restricted to treatment-seekers and studies in non-treatment seeking cocaine abusers are sparse. Here, we assessed GM volume differences between 30 non-treatment-seeking cocaine-dependent individuals and 33 non drug using controls using voxel-based morphometry (VBM). Additionally, within the group of non-treatment-seeking cocaine-dependent individuals, we explored the role of frequently co-occurring features such as of trait impulsivity (Barratt Impulsivity Score, BIS), smoking, depressive symptoms (Beck Depression Inventory (BDI), as well as the role of cocaine use duration, on frontal GM volume. Smaller GM volumes in non-treatment-seeking cocaine-dependent individuals were observed in the left middle frontal gyrus. Moreover, within the group of cocaine users, trait impulsivity was associated with reduced GM volume in the right OFC, the left precentral gyrus and the right superior frontal gyrus, whereas no effect of smoking severity, depressive symptoms or duration of cocaine use was observed on regional GM volumes. Our data show an important association between trait impulsivity and frontal GM volumes in cocaine-dependent individuals. In contrast to previous studies with treatment-seeking cocaine-dependent patients, no significant effects of smoking severity, depressive symptoms or duration of cocaine use on frontal GM volume were observed. Reduced frontal GM volumes in non-treatment-seeking cocaine-dependent subjects are associated with trait impulsivity and are not associated with co-occurring nicotine dependence or depression.